Pengaruh Gaya Kepemimpinan dan Disiplin Kerja terhadap Motivasi Kerja Serta Dampaknya pada Kinerja Pegawai Dinas Pendidikan dan Kebudayaan Kabupaten Merangin - Rahmayeni, Weni; MS, M. Zahari; Hapsara, Osrita (J-MAS (Jurnal Manajemen dan Sains), 2024)
The purpose of this research is to describe leadership style, work discipline, motivation and performance of employees of the Merangin Regency Education and Culture Service and to analyze the influence of leadership style and work discipline partially and simultaneously directly and indirectly on employee work motivation and performance, as well as to analyze work motivation on employee performance. To answer the research objectives, this research is supported by theoretical studies related to research variables, namely leadership style, work discipline, work motivation and performance. Apart from that, the author also looked for relevant previous research in the form of articles/journals and previous theses to support this research. The population in this research is ASN employees totaling 73 employees with conditions in 2022. The data analysis technique used in this research is through path analysis followed by hypothesis testing through the F test (Simultaneous) and t test (Partial). From the path analysis tests carried out, it was found that leadership style and work discipline influenced work motivation by 46.28% while the rest was influenced by other variants. Leadership style and work discipline have an influence of 43.14% on employee performance at the Merangin Regency Education and Culture Office. This research concludes that leadership style, work discipline, work motivation and employee performance are in good and high condition. Apart from that, work discipline and work stress partially and simultaneously have a positive and significant influence on work motivation and employee performance at the Merangin Regency Education and Culture Office. Likewise, work motivation has a positive and significant influence on employee performance.